Kajian Teknis Perencanaan Penggantian Lampu Penerangan Jalan Umum Lampu Son-T Ke Led Di Jalan Jenggolo Asri - Randu Asri Sidoarjo - Gia Edu Fialdy; Aris Heri Andriawan (Pusat Riset dan Inovasi Nasional, 2023)
Street lighting is a safety infrastructure on the highway. However, currently most of the public street lighting lamps do not comply with the provisions of the Indonesian National Standards Agency (BSNI). It is necessary to plan for lamp replacement by using lamps that are appropriate to field conditions, so that the light intensity produced is in accordance with established standards. Jalan Jenggolo Asri - Randu Asri in Sidoarjo is an example of a road that requires planning for lighting changes. This road is a type of secondary collector road with a length of 2500 meters and a road width of 6 meters. The lighting on this road does not meet the standards set by BSNI 7391: 2008 caused by several lights that go out and the power of the lights used is not optimal. Planning for replacing public street lighting is needed on this road by recalculating the maximum light intensity requirements. The method that can be done is to replace the lamp used with an LED lamp. In the current initial conditions, street lighting on this road uses 250W SON and 150W LED lamps. After planning, the lights will be replaced with 100W LED lights. The planning results show that by using a 100W LED lamp, a handlebar ornament angle of 14.06° will be produced, the light intensity is Candela, the lighting intensity is 6.77 Lux, and the power required per day is 26.4 kWh. Comparison with the use of 250 Watt SON lamps shows that the use of 100W LED lamps is more efficient in energy consumption by 51.76%. The results of this planning have met the standard requirements for secondary collector roads. Thus, by replacing the lights according to the plan, it is hoped that street lighting on Jalan Jenggolo Asri - Randu Asri Sidoarjo can meet the standards set by BSNI 7391:2008 and provide optimal light intensity with more efficient energy use.